Jual Beli dalam Perspektif Islam: Analisis Konsep, Prinsip, dan Implementasinya dalam Transaksi Kontemporer - Surya Bakti; Hafiz Fadillah; Khanaya Abhita Putri; Lukman Afif; Lola Armeita; Muhammad Imam (Yayasan Zia Salsabila, 2026)
The development of digital technology has transformed buying and selling practices from conventional to electronic-based transactions. This situation demands a study of the relevance of the concept of buying and selling in Islam to various forms of contemporary transactions. This study aims to analyze the concept of buying and selling in Islam, the pillars and conditions for valid buying and selling, prohibitions in transactions, and its implementation in digital transactions. The study used a qualitative approach with a library research method. Data were obtained from the Qur'an, Hadith, books on Islamic jurisprudence (fiqh muamalah), scientific books, fatwas of the National Council of Indonesian Ulema Council (DSN-MUI), and relevant journal articles, then analyzed using content analysis techniques. The results show that the concept of buying and selling in Islam remains relevant to be applied in the digital era as long as it meets the pillars and conditions of buying and selling and avoids elements of usury (riba), gharar (gharar), maisir (maysir), and tadlis (tadlis). Various contemporary transactions, such as marketplaces, e-commerce, cash on delivery (COD), dropshipping, affiliate marketing, live shopping, digital products, e-wallets, and QRIS, are essentially permitted as long as they comply with sharia principles and the provisions of the DSN-MUI fatwas. Thus, the principles of buying and selling in Islam remain the guiding principle for realizing a fair, transparent, and welfare-oriented digital trading system.